To investigate and diagnose the engine problems and used it as a study purpose / Abdul Habib Muhamad Fuzi and Ahmad Najib Abu Bakar - Muhamad Fuzi, Abdul Habib; Abu Bakar, Ahmad Najib (2000)
As an auto mechanic, we will need knowledge, diagnostic skills and repairing skills. As a mechanic, we must check automotive systems to find the causes of many kinds of problems. But that is nit enough. We must check related systems and components to be sure that the problems will not occur against. This kind of checking requires a skill called diagnosis. In this project, we got an old engine model Triumph Spitfire Mk4 (1296 cc) and it's in a poor condition. Two of the cylinders, i.e. cylinder 1 and 2 are rusted and piston number 3 and 4 are seized. The cylinder liners are full of water. From the history of the engine, we come to know that the engine was overheating while running. So we need to find out, why and where are these problems occur. From our diagnose, we found that the cause of this problem is coming from the COOLING SYSTEM. Hence, we investigate the cooling system and try to find out the problems by the help of the symptom from the engine. This engine is an old model design and has a simple arrangement. Therefore, we want to use the major parts of the engine as a study purpose for other students who want to know about the systems in the engine. We hope that it will be a useful learning material to the next UiTM students.